Photophysiology And Photoprotection Of Marine Microalgae Communities In Northern Straits Of Malacca And Antarctic Peninsula - Mohd Zainudin, Muhamad Hilal (2020)
Marine microalgae play a significant role in global primary productivity in coastal marine ecosystem. The introduction of active fluorometer such as the Pulse Amplitude Modulation (PAM) fluorometer in the 1980s allows measurements photosynthetic parameters in the field. This provides valuable information of microalgae on their responses to different environmental and nutrient conditions. This thesis investigates the community structure and photo-physiology conditions of tropical and polar microalgae and their responses to varying irradiance regimes. It is hypothesized that microalgae composition in tropical and polar will be affected by various environmental variables. Sample was collected from five stations in the Northern Straits of Malacca was conducted in November and December 2015 (wet phase) and February 2016 (dry phase) which started from CEMACS USM, Pulau Pinang to Pulau Songsong, Kedah.